Performance analysis of proposed local link repair schemes for ad hoc on demand distance vector. Issue 2 (1st June 2014) - Jain, Jyoti; Gupta, Roopam; Bandhopadhyaya, Tushar K.
Abstract : Reactive routing protocols are better options for the communication in ad hoc network. In this study, a novel approach for local link repairing of ad hoc on demand routing protocol is suggested for the performance enhancement of the basic protocol. Alternate route finding for next‐to‐next node in case of link breakage is a better option of route management. These protocols are beacon‐less to improve bandwidth utilisation. Control overheads have been reduced by using 802.11b protocol to maintain connectivity of moving nodes. Significant improvement is observed in the Quality of service parameters like throughput, end‐to‐end delay, packet delivery ratio and link breakage through simulations.